Reduction of waste generation using lean manufacturing in a peruvian craft brewery. An empirical review - Espinoza Berrocal, Roman Alejandro (2024)
The craft brewery sector is growing in the alcoholic beverage market; however, they face high costs and limitations that limit its growth. This is because companies in this sector are SMEs and need to be more efficient in their efforts. The main causes of the generation of waste that affects the profitability of the company are non-standard work procedures, inadequate plant design, and poor order and cleanliness. For this reason, this research aims to reduce waste generation through the implementation of Lean Manufacturing tools: Standard Work, 5S and Poka Yoke, and Systematic Layout Planning (SLP). To validate the success of the implementation of these tools, the simulation software was used. The validation consisted in two scenarios, the current and the proposed with improvement. After the simulation, the results were the following: first, the amount of wasted beer was reduced from 5,029 litres to 2,3708 litres. secondly, efficiency increased from 76.14% to 82.17%. The loss of annual sales due to waste was reduced from PEN 179,030.35 to PEN 83,173.90. Therefore, the project is considered as successful.